The adoption of happy-seeder technology by 0.5 million farm-households on 1.3 million hectares in north-west India contributed to increased yields, profits, water and nutrient saving. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In continuation of CCAFS outcome reported during 2017 and 2018, significant efforts made during 2019 through science evidence mediated enabling environments, enhanced capacity and community awareness through innovative partnerships and investments, lead to significantly increased adoption of no-burn, happy seeder technology reaching 1.3 million hectares of north-west India and to more than ~0.5 million farmers. However, urban and rural beneficiary population due to reduced air pollution are quite significant and estimated at 50 million.